The art of deduction: Holmes’ mark on the media - Beeche Antezana, Sergio (2026)
The present article has the intention to analyzethe characteristics, relationships and audiovisual representations of famous literary character Sherlock Holmes,created by British writer Sir Arthur Conan Doyle.Taking the classic writings to make relevant compari-sons with the most recent adaptation from British tele-vision, noting that a different perspective can give greatinnovation of ideas, characters and scenarios.